EQUALITY TOWARDS A CIVIL SOCIETY: ANALYSIS OF INDIVIDUAL QUALITY TOWARDS SEYYED ALI KHAMENEI'S NATIONAL IDENTITY - Riko Putra (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2024)
Society is a universal foundation for state formation. Living in a diverse national context involves navigating social constructs such as race, nationality, and the relationship between religion and state, including critical issues like gender equality. This necessitates a positive lifestyle aligned with the concept of a civil society, which promotes an advanced and civilized way of life with tolerance and democracy. This research examines how Iran’s supreme leader, Seyyed Ali Khamenei, fosters a civil society in the context of gender equality. The study critically analyzes literature using a qualitative approach that assesses the influence of a leader's national identity based on reviews of policies, thoughts, fatwas, and speeches. A theo-democratic ideology shapes Iran’s national identity through Wilāyat al-Faqīh, which governs the judicial, executive, and legislative branches. Seyyed Ali Khamenei, who has been Iran's third president and continues as its leader, significantly influences this identity. The findings reveal that Khamenei's approach to national identity in promoting a civil society amid gender equality issues grants Iranian women a dignified role, appropriate for Muslim women, by facilitating their participation in the public sphere while preserving religious and cultural values as part of the national identity.